The Commonwealth of Independent States and the Problems of Eurasian Integration - K. P. Borishpolets; S. Chernyavsky (Международная аналитика, 2015)
The current situation on the territories neighboring to Russia is characterized by a high degree of turbulence in the sphere of international interaction. A dynamic “mixture” of positive and negative (from the viewpoint of international security and sustainable economic growth) phenomena, intensification of international interaction against the background of strengthening international competition have led to the formation in 2014-2015 of a specific amalgamation of traditional, modern, and brand new trends in the development of Russia and her close neighbors.In the context of integration processes in Eurasian space, the multilateral cooperation within the CIS and EAEU formats presupposes a consolidation of all members’ efforts to realize common goals. As far as Russia is concerned, her regional leadership is equal to the ability to serve as a model for typologically similar countries. The primary and most important condition of retaining Russia’s influence upon both the CIS countries and the world community as a whole is an exemplary decision of problems of her own development, taking also into consideration the necessity to oppose external challenges.